Tinjauan Etika Bisnis Islam terhadap Praktik Jual Beli Sistem Preloved pada Shopee - Nisrina Jameela; Eva Misfah Bayuni; Nanik Eprianti (Bandung Conference Series: Sharia Economic Law, 2024)
Abstract. Buying and selling is a form of social interaction that is often carried out by all humans. Doing business must adhere to the basic principles of Islamic business ethics. Business and ethics should not be seen as two opposing things in Islamic economics, in fact buying and selling using online systems tends to ignore ethics. Even though there are many free trade ideas emerging, debates and competition which ultimately give rise to enthusiasm among business people to justify various ways of selling their products in online shops. Prelovedboo online shop buying and selling practices on Shopee describe the product as having "no minuses" but after the product arrives to the buyer there are stains. This research uses qualitative methods, with data collection techniques through interviews, documentation, literature study, and observation, then with data analysis techniques, namely data reduction, data presentation, and drawing conclusions. The results of this research are reviewed from the basic principles of Islamic business ethics, regarding the Islamic business ethics implemented by Prelovedboo at Shopee revealing business practices that reflect the basic principles of Islamic business ethics. The shop owner, Salsabila Hana, runs a business by integrating ethical business values into every aspect of its operations. However, Islamic business ethics regarding buying and selling Prelovedboo on Shopee does not meet the principles of Islamic business ethics, namely at the balance point where the Prelovedboo online shop is not specific in providing descriptions of goods sold on Shopee. This can be a challenge in implementing the principles of balance or fairness, because buyers must be able to trust the information provided by the seller. Abstrak. Jual beli merupakan bentuk interaksi sosial yang sering dilakukan semua manusia. Berbisnis harus berpegang pada prinsip-prinsip dasar etika bisnis Islam. Bisnis dan etika tidak boleh dilihat sebagai dua hal yang berlawanan dalam ekonomi Islam, dalam kenyataannya jual beli yang menggunakan sistem online cenderung mengabaikan etika. Bahkan sekalipun ada banyak muncul gagasan perdagangan bebas, perdebatan, dan persaingan yang pada akhirnya memunculkan gairah dari para pembisnis untuk menghalalkan berbagai cara dalam menjual produknya di online shop. Praktik jual beli online shop Prelovedboo di Shopee mendeskripsikan produk “no minus” namun setelah produk sampai kepada pembeli terdapat noda. Penelitan ini menggunakan metode kualitatif, dengan teknik pengumpulan data melalui wawancara, dokumenasi, studi pustaka, dan observasi, kemudian dengan teknik analisis data yaitu reduksi data, penyajian data, dan penarikan kesimpulan. Hasil penelitian ini ditinjau dari prinsip-prinsip dasar etika bisnis Islam, mengenai etika bisnis Islam yang diterapkan oleh Prelovedboo di Shopee mengungkapkan praktik bisnis yang mencerminkan prinsip-prinsip dasar dalam etika bisnis Islam. Pemilik toko, Salsabila Hana, menjalankan bisnis dengan mengintegrasikan nilainilai etika bisnis dalam setiap aspek operasionalnya. Namun, etika bisnis Islam terhadap jual beli online shop Prelovedboo di Shopee belum memenuhi prinsip etika bisnis Islam yaitu pada poin keseimbangan dimana online shop Prelovedboo tidak spesifik dalam memberikan deskripsi barang yang dijual di Shopee. Hal ini dapat menjadi tantangan dalam menjalankan prinsip keseimbangan atau keadilan, karena pembeli harus dapat mempercayai informasi yang diberikan oleh penjual.